Amaranthus grain as a new ingredient in diets for dairy cows: productive, qualitative, and in vitro fermentation traits. (22nd January 2022) - Calabrò, Serena; Oteri, Marianna; Vastolo, Alessandro; Cutrignelli, Monica Isabella; Todaro, Massimo; Chiofalo, Biagina; Gresta, Fabio
Abstract: BACKGROUND: In recent decades, grain amaranths have attracted attention due to their valuable combination of nutritional traits, with higher protein and oil content than conventional cereals. Before they can be proposed as an unconventional ingredient in animal feed, many aspects still need to be investigated from field production to nutritive value. The present research aimed to study the agronomic traits, proximate composition, and digestibility/degradability, fatty acid profile, antioxidant activity, and total phenolic content of two grain amaranth species, Amaranthus cruentus and Amaranthus hypochondriacus (for a total of six accessions), grown in a Mediterranean environment. RESULTS: Both species showed seed yields comparable to or higher than the traditional cereal crops in the same environment. On the whole, A. cruentus resulted in a higher seed production than A. hypochondriacus . Mexico and Montana accessions, both belonging to A. cruentus, showed the highest yield (3.73 t ha −1, on average). Few differences emerged in nutritive value between species and accessions: the Illinois accession of A. cruentus showed the best performance in terms of in vitro degradability and gas production, but not for volatile fatty acid production; the fermentation kinetics was slowest in the Illinois accession and fastest in the Montana accession of A. cruentus and the India accession of A. hypochondriacus . CONCLUSION: From a health perspective, the Nebraska accession of A. hypochondriacus represents the best accession, with the lowest saturated fatty acid content and the highest polyunsaturated fatty acid content. © 2022 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.